Perspectives in Super-Resolved Fluorescence Microscopy: What Comes Next? - Cremer, Christoph; Birk, Udo (Frontiers in Physics, 2016)
The Nobel Prize in Chemistry 2014 has been awarded to three scientists involved in the development of STED and PALM super-resolution fluorescence microscopy (SRM) methods. They have proven that it is possible to overcome the hundred year old theoretical limit for the resolution potential of light microscopy (of about 200 nm for visible light), which for decades has precluded a direct glimpse of the molecular machinery of life. None of the present-day super-resolution techniques have invalidated the Abbe limit for light optical detection; however, they have found clever ways around it. In this report, we discuss some of the challenges still to be resolved before arising SRM approaches will be fit to bring about the revolution in Biology and Medicine envisaged. Some of the challenges discussed are the applicability to image live and/or large samples, the further enhancement of resolution, future developments of labels, and multi-spectral approaches.